Dime quién fui - Rodríguez Court, Elisa, 1959- (Madrid : Editorial Verbum, 2015)
Isa, the narrator, tells the story of the last years of her father's life, a man who was basically unknown to her, as he had abandoned her family when she was a child.
A novel.
Online resource; title from PDF title page (Digitalia, viewed September 27, 2016)
Keywords: Father and child -- Fiction; Families -- Fiction; Death -- Fiction; Novels; Fiction; Electronic books